An introduction to counselling and psychotherapy : theory, research, practice, and social purpose / John McLeod. - McLeod, John, 1951- (Open University Press, 2025)
A comprehensive introduction to the research and practice of counselling and psychotherapy and enables students to develop their confidence in deploying a range of therapeutic models. With renewed focus on issues of social justice and in-depth consideration of how best to respond to contemporary developments within and beyond the therapy session McLeod's most recent edition provides students with the skills required to navigate their early careers in a post-COVID 19 context.